2021
DOI: 10.1016/j.jdent.2021.103749
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and its global effects on dental practice. An International survey

Abstract: Objectives A multicentre survey was designed to evaluate the impact of COVID-19 outbreak on dental practice worldwide, estimate the COVID-19 related symptoms/signs, work attitudes and behaviour and the routine use of protective measures and personal protective equipment (PPE). Methods A global survey using a standardized questionnaire with research groups from 36 countries was designed. The questionnaire was developed and pretested during April 2020 and contained three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 29 publications
5
42
0
Order By: Relevance
“…In this study, the participation rate of 14.1% is in line with that of some surveys dealing with COVID-19 infection among dentists [13,15] but lower than other publications in recent literature [14,24,26]. The fact that the survey was launched during summer 2020 when the majority of the dentists had resumed their activities, thus being very busy with patient treatments and the fact that the survey was carried out in the holiday period, might have influenced the rate of participation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, the participation rate of 14.1% is in line with that of some surveys dealing with COVID-19 infection among dentists [13,15] but lower than other publications in recent literature [14,24,26]. The fact that the survey was launched during summer 2020 when the majority of the dentists had resumed their activities, thus being very busy with patient treatments and the fact that the survey was carried out in the holiday period, might have influenced the rate of participation.…”
Section: Discussionsupporting
confidence: 86%
“…Few national studies have investigated the level of infection among dentists, which, in its turn, is associated with dentists' knowledge, attitudes, perceptions, and awareness of viral transmission in daily practice [12][13][14]. A recent study including data from 36 countries showed that the reported routine use of FFP2/N95 masks was the only measure significantly associated with a reduced risk of viral infection acquisition by dentists [15].…”
Section: Introductionmentioning
confidence: 99%
“…Data presented in this survey are part of the 2020 International Collaborative COVID-19 Disease Study, with a previously registered protocol at the World Pandemic Research Network (WPRN) WPRN-486352 [9]. The central management team of COVIDental Collaboration Group invited 36 collaborating research groups worldwide [10]. According to the protocol designed by the central coordinator (GC) and his team, our research team sent 13 invites to the collaborators from other countries geographically corresponding to the Southeastern Europe.…”
Section: Methodsmentioning
confidence: 99%
“…The structured and closed cross-sectional survey was developed using a previously standardized questionnaire available as supplement material in a previously published paper by the wider international team [10]. The questionnaire was designed by modified Delphi method and involved the following domains: (1) general data (personal, demographic, and working status); (2) data regarding COVID-19 infection rate and symptoms; and (3) use of preventive and prophylactic measures, PPE, and risk perception [9,10]. The study protocol was previously pretested on 12 dentists; only items showing Intra-class Correlation Coefficient higher than 0.80 were further tested and evaluated among 3599 dentists in North Italy in April 2020 [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation